Impact of minimum bid requirement of Japan's electricity market on virtual power plant's profit - Reza Nadimi; Masahito Takahashi; Koji Tokimatsu; Mika Goto (Heliyon)
In the context of small-scale virtual power plants (VPPs), the minimum power requirement (MPR) poses a significant challenge for market participation due to the inherent volatility and uncertainty associated with renewable energy sources. To mitigate this, a VPP system can potentially enhance its profitability by utilizing an Internal MPR, which is a value derived from market prices and historical data, including actual and forecasted renewable power generation, and is typically lower than the market MPR. This study investigates several market strategies, designated as Plans II, III, and V, under hypothetical conditions, and evaluates their impact on the profitability of VPPs relative to existing strategies (Plans I and IV) within the Japan Electric Power eXchange (JEPX) market. Currently, the MPR for day-ahead (DA) and intraday (ID) markets is set at 0.1 MW per settlement period. This research involves the simulation of all five plans across 11 small-scale VPP systems, with capacities ranging from 0.05 MW to 1 MW. The simulation results indicate that reducing the market MPR to 0.04 MW for both DA and ID markets results in increased profitability for VPPs. The findings of this study suggest potential policy implications for Japan's power market, emphasizing the benefits of adjusting MPR thresholds to better accommodate the participation of small-scale VPPs and enhance overall market efficiency.